Dietary Bioactives for Modulation of Blood Pressure and Mitigation of Cardiovascular Risk: Review Article (Journal of Pharma Insights and Research, 2025)
Cardiovascular disease (CVD) is one of the major causes of global morbidity and mortality, with systemic arterial hypertension constituting its most significant modifiable risk factor. Elevated blood pressure drives pathophysiological processes like vascular remodeling, endothelial dysfunction, and chronic inflammation, culminating in myocardial infarction and stroke. Dietary nutraceuticals, which are bioactive compounds derived from functional foods and plant extracts, offer compelling, accessible avenues for mitigating these underlying pathologies. The main compounds, including omega-3 fatty acids, organosulfur compounds (from Allium sativum), catechins (from Camellia sinensis), and curcuminoids (from Curcuma longa), show notable antihypertensive and cardioprotective effects. These beneficial actions are primarily mediated through enhanced nitric oxide bioavailability, modulation of the Renin-Angiotensin-Aldosterone System (RAAS), and reduction of systemic oxidative stress. Moreover, specific phytochemicals like anthocyanins (found in berries) and nutrients such as potassium (high in kiwifruit) contribute positively to improving vascular compliance and maintaining critical electrolyte balance. The existing evidence, derived from epidemiological data and randomized controlled trials, suggests a supportive role for these agents. However, rigorous future investigation is required to establish standardized dosages, optimal formulations, and long-term clinical outcomes. These dietary components are powerful, accessible complements to conventional therapeutic options for primary and secondary CVD prevention